Private Sector Unions and Strategic Planning: A Research Agenda - Stratton, Kay; Reshef, Yonatan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
Private sector North American trade unions have declined in recent years. This paper argues that to prevent further erosion, unions should engage in strategic planning. Further, it highlights the importance of resource analysis to predict a union's likelihood to strategically plan, and presents relevant research hypotheses.